Desarrollo de un modelo de mejoramiento continuo de atención al cliente en el Servicio Ecuatoriano de Capacitación Profesional SECAP a nivel nacional en el Ecuador - Garcés Núñez, Mauricio Gonzalo (2014)
This research will encourage the technical knowledge and contain definitions and analysis tools provided for in the models of continuous improvement and service customer on issues concerning quality, since from them we can determine the way forward for growth and transformation of care provided to the client in the Ecuadorian Professional Training (SECAP). From the above, the application of a model of continuous improvement in the area of customer service improve satisfaction levels and quality in service delivery. With this context aims to increase organizational performance and ensure that citizens receive quality service while contributing to the Ecuadorian Professional Training (SECAP) to become a leading institution in the national technical training service for productive and social sectors. With technical analysis of current service levels can be determined on which aspects should be focused and work on continuous improvement model, which can also be applied to any business, especially in those who are in services.